Are your tax problems an opportunity not to pay taxes? Evidence from a randomized survey experiment - Sebastian Blesse (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Taxpayers often view tax rules and filing processes as complicated. In this paper I study whether the perceived tax uncertainty among peers leads to a reduction of voluntary tax compliance. I find strong supportive evidence for this hypothesis using a survey experiment for a large representative sample of the German population. Providing randomized information that others are uncertain about how to file their taxable income decreases individual tax morale. This suggests that subjects use negative peer signals as an excuse in order to opt-out of tax compliance. Studying related heterogeneous treatment effects, I find that both older and left-wing subjects are more responsive to tax uncertainty of others. I also show persistent treatment effects among very honest taxpayers in a follow-up survey.
Keywords: H26; Z13; K42; C9; 330; Tax Complexity; Taxpayer Uncertainty; Tax Morale; Survey Experiments